Hemibates koningsi spec. nov: a new deep-water cichlid (Teleostei: Cichlidae) from Lake Tanganyika - Schedel, Frederic Dieter Benedikt; Schliewen, Ulrich Kurt (Zootaxa, 2017)
Hemibates koningsi, new species, is described from southern Lake Tanganyika (Republic of Zambia) as the second species of Hemibates Regan, 1920. Males of the new species are easily distinguished from H. stenosoma (Boulenger, 1901) based on their adult color pattern, i.e. black vertical bars on the anterior flanks part and posterior horizontal bands on a silvery-whitish body coloration vs. an anterior flank color pattern of black blotches of variable number, size and shape and posterior horizontal bands. Males and females of the new species are further distinguished by their longer lower pharyngeal jaw (37.6–38.2% HL vs. 27.8–32.5% HL) with a characteristically curved keel, which is straight or only slightly curved towards the tips in H. stenosoma. The new species has on average fewer gill rakers on the first gill arch than its only congener (33–37 vs 35–43).